REMOTE SIMULATOR DEVELOPMENT FOR RIS (RIVER INFORMATION SERVICE) OPERATORS - Кульбацкий, Андрей (SWorldJournal, 2021)
River Information Services is the concept for information services in inland navigation to support traffic and transport management in inland navigation, including interfaces to other transport modes. The potential of RIS to put inland navigation in a bet